Sulfurized polyacrylonitrile material and its lithium-sulfur battery positive electrode, lithium-sulfur battery
By preparing vulcanized polyacrylonitrile material with strong bonding and conjugation system, combining conductive agents and MXene materials, the problem of unstable sulfur positive electrode of lithium-sulfur batteries is solved, and high cycle stability and capacity retention of lithium-sulfur batteries are achieved. Rate.
Patent Information
- Application Number
- CN202210895792.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-07-27
AI Technical Summary
The existing sulfur positive electrodes of lithium-sulfur batteries are unstable during charging and discharging, and there are problems of soluble intermediates and volume expansion, which limits the development and application of lithium-sulfur batteries.
By preparing vulcanized polyacrylonitrile material with strong bonding and conjugation system, combining conductive agents and MXene materials, a high-performance lithium-sulfur battery positive electrode material is made to improve the load capacity and conductivity of the electrode.
It improves the cycle stability and capacity retention rate of lithium-sulfur batteries, alleviates volume expansion during charging and discharging, and improves the overall performance of the battery.
Smart Images

Figure CN115304797B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and particularly relates to a sulfurized polyacrylonitrile material, a lithium-sulfur battery positive electrode, and a lithium-sulfur battery. Background Art
[0002] Energy is the cornerstone of human survival and development. With the rapid growth of the world's population and the increasing economic growth of each country, the demand for energy is getting higher and higher. However, the increasingly serious environmental pollution problem is a huge threat to the sustainable development of mankind. Therefore, it is crucial to find green and environmentally friendly clean energy, and developing a secondary battery system with high energy density, long life, and low cost has become a current research hotspot. Lithium-ion batteries are currently the best commercialized secondary battery system. However, with the popularization of new energy vehicles and the rapid development of more safe and efficient electronic devices, the existing lithium-ion batteries can no longer meet the needs of the public, and there is an urgent need to develop a new battery system with higher specific energy.
[0003] Lithium-sulfur batteries have attracted much attention because of their theoretical specific capacity of 1675 mAh g -1 , and the theoretical energy density of 2600 Wh kg -1 . In addition, sulfur is abundant in nature, relatively low in cost, and environmentally friendly. Therefore, lithium-sulfur batteries have broad application prospects. However, there is still a large room for development in commercializing lithium-sulfur batteries. At present, the sulfur positive electrode of lithium-sulfur batteries is unstable during charge and discharge, and there are many soluble intermediates polysulfides (Li2S n , 3 < n < 8) during charge and discharge. Elemental sulfur and its discharge products (Li2S2 and Li2S) are electron and ion insulators, which will cause about 80% volume expansion of elemental sulfur during charge and discharge to form lithium sulfide. The above problems greatly limit the development and application of lithium-sulfur batteries.
[0004] As a positive electrode material with a solid-solid transfer mechanism, sulfurized polyacrylonitrile (S@PAN) has good cycle performance, high cycle specific capacity, high Coulomb efficiency, and low self-discharge rate. As a sulfur-containing positive electrode material, sulfurized polyacrylonitrile can stably exist in the electrolyte and participate in the cycle of lithium ions, and there is no "shuttle effect" of lithium-sulfur batteries. Therefore, it is a very promising positive electrode material for lithium-sulfur batteries.
[0005] In the prior art, sulfurized polyacrylonitrile is generally prepared by directly heating a mixture formed by polyacrylonitrile and sulfur. The obtained sulfurized polyacrylonitrile has fewer conjugated bonds and a low degree of cyclization. Using it as the positive electrode material of a lithium-sulfur battery, the cycle performance of the battery needs to be further improved. Summary of the Invention
[0006] The first object of the present invention is to provide a method for preparing a sulfurized polyacrylonitrile material. The second object of the present invention is to provide a sulfurized polyacrylonitrile material obtained by the preparation method. The third object of the present invention is to provide a method for preparing a positive electrode of a lithium-sulfur battery. The fourth object of the present invention is to provide a positive electrode of a lithium-sulfur battery obtained by the preparation method. The fifth object of the present invention is to provide a lithium-sulfur battery.
[0007] According to a first aspect of the present invention, there is provided a method for preparing a vulcanized polyacrylonitrile material, comprising the following steps:
[0008] (1) adding sodium lauryl sulfate into water and stirring to obtain a first mixed solution;
[0009] (2) adding potassium persulfate to the first mixed solution and continuing stirring to obtain a second mixed solution;
[0010] (3) heating the second mixed solution until the solution temperature reaches 70° C., adding acrylonitrile, stirring the whole process and passing nitrogen, maintaining 65-70° C. for 1-1.5 hours, and obtaining a polyacrylonitrile solution after the reaction is completed;
[0011] (4) centrifuging the polyacrylonitrile solution and freeze-drying the solid product obtained by centrifugation to obtain polyacrylonitrile;
[0012] (5) Mixing polyacrylonitrile and sulfur powder and subjecting them to high-temperature heat treatment to obtain a sulfurized polyacrylonitrile material.
[0013] The reaction principle of the present invention is:
[0014] Sodium lauryl sulfate is a kind of surfactant, and its long chain has stronger adsorption to the surface of acrylonitrile nanoparticles, so that acrylonitrile monomer can carry out emulsion polymerization. The sulfate radical free radical produced by potassium persulfate initiator activation under heated state attacks the double bond of acrylonitrile monomer, forms methylene free radical, and then methylene free radical and acrylonitrile monomer molecule add rapidly, thereby forms macromolecular free radical. Along with the continuation of polymerization reaction, the methylene free radical of different reaction monomers can combine with each other, thereby forms high molecular weight polymer. Oxygen can prevent the generation of polymerization reaction, therefore, the present invention needs nitrogen protection in reaction process, and reaction is carried out under oxygen-free condition.
[0015] In some embodiments, the mass ratio of sodium dodecyl sulfate, water, potassium persulfate, and acrylonitrile is (0.5-4):100:0.1:5.
[0016] In some embodiments, the mass of sodium dodecyl sulfate is (0.5-4) g, the mass of water is 100 g, the mass of potassium persulfate is 0.1 g, and the mass of acrylonitrile is 5 g.
[0017] In some embodiments, the acrylonitrile is added dropwise within 5 minutes.
[0018] In some embodiments, the mass ratio of polyacrylonitrile to sulfur powder is 1:4.
[0019] In some embodiments, the high temperature heat treatment is performed at a temperature of 300-600° C. and a time of 6-8 hours.
[0020] In some embodiments, polyacrylonitrile and sulfur powder are fully ground, dried in a vacuum drying oven at 60° C. for 24 hours, and then subjected to high-temperature heat treatment at 300° C. for 6 hours in an argon atmosphere.
[0021] In some embodiments, the stirring is magnetic stirring, and the stirring speed is 200-400 rpm.
[0022] In some embodiments, the sulfur powder is sublimated sulfur.
[0023] According to a second aspect of the present invention, there is provided a sulfurized polyacrylonitrile material obtained by the above-mentioned preparation method.
[0024] According to a third aspect of the present invention, there is provided a method for preparing a positive electrode of a lithium-sulfur battery, comprising the following steps:
[0025] The above-mentioned sulfurized polyacrylonitrile material is mixed with a conductive agent, an oily binder, or a conductive agent, a MXene material and an aqueous binder and ball-milled to prepare an electrode slurry, and then the slurry is evenly coated on a current collector and dried to obtain a lithium-sulfur battery positive electrode.
[0026] In some embodiments, the above-mentioned sulfurized polyacrylonitrile material, the conductive agent, and the oily binder are ball-milled in an organic solvent to prepare an electrode slurry, and then the slurry is evenly coated on a current collector and dried to obtain a lithium-sulfur battery positive electrode.
[0027] In some embodiments, the conductive agent is Super P, the oily binder is polyvinylidene fluoride (PVDF), and the organic solvent is N-methylpyrrolidone.
[0028] In some embodiments, the mass ratio of the vulcanized polyacrylonitrile material to the conductive agent and the oily binder is 7:2:1.
[0029] In some embodiments, the slurry is uniformly coated on the current collector using a 500 μm doctor blade.
[0030] In some embodiments, the current collector is a metal-based current collector selected from aluminum foil.
[0031] In some embodiments, the above-mentioned sulfurized polyacrylonitrile material is ball-milled with a conductive agent, a MXene material, and an aqueous binder in an aqueous solvent to prepare an electrode slurry, and then the slurry is uniformly coated on a current collector and dried to obtain a lithium-sulfur battery positive electrode.
[0032] In some embodiments, the conductive agent is Super P, the concentration of the MXene material is 5 mg / mL, and the aqueous binder is polyacrylate.
[0033] In some embodiments, the mass ratio of the sulfurized polyacrylonitrile material to the conductive agent, the MXene material, and the aqueous binder is 16:1:1:2.
[0034] In some embodiments, the slurry is uniformly coated on the current collector using a 750 μm doctor blade.
[0035] In some embodiments, the current collector is a metal-based current collector selected from aluminum foil.
[0036] According to a fourth aspect of the present invention, a lithium-sulfur battery positive electrode prepared by the above preparation method is provided.
[0037] According to a fifth aspect of the present invention, a lithium-sulfur battery is provided, which is composed of the above-mentioned lithium-sulfur battery positive electrode, lithium metal negative electrode plate, polypropylene separator and electrolyte. Exemplarily, the assembly method of the lithium-sulfur battery is: assembling the above-mentioned lithium-sulfur battery positive electrode, lithium metal negative electrode plate, polypropylene separator and electrolyte into a 2016 model battery in an argon glove box with a water content of less than 10ppm, wherein the composition of the electrolyte is: 1 mol / L lithium bistrifluoromethylsulfonyl imide 1,3-dioxolane / ethylene glycol dimethyl ether, wherein the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:1.
[0038] The beneficial effects of the present invention include:
[0039] (1) The present invention utilizes the characteristics of acrylonitrile containing double bonds and triple bonds. By regulating the reaction conditions, the synthesized sulfurized polyacrylonitrile material simultaneously has hydrogen bonds, double bonds and triple bonds. The product has strong bonding force, which is beneficial to the increase of the active material loading of the electrode, and can promote the uniform dispersion of the conductive agent and the active material in the slurry and firmly bond to the current collector, which can alleviate the volume effect during the charging and discharging process of the lithium-sulfur battery to the greatest extent.
[0040] (2) The present invention regulates the reaction conditions so that polyacrylonitrile undergoes a cyclization reaction during the reaction between polyacrylonitrile and sulfur, thereby making the formed sulfurized polyacrylonitrile a conjugated polymer with a conjugated system. The conjugated polymer is used as the positive electrode material of the lithium-sulfur battery, which can avoid the dissolution of polysulfides during the charge and discharge process of the lithium-sulfur battery and has a higher charge and discharge specific capacity.
[0041] (3) Battery cycle tests show that the battery assembled using the sulfurized polyacrylonitrile material of the present invention has a high first-cycle charge and discharge capacity, high coulombic efficiency, and excellent capacity retention rate. Most importantly, it can make the lithium battery have good cycle stability.
[0042] (4) The present invention can maintain the conductive properties of the lithium-sulfur battery, alleviate the volume expansion during the charge and discharge process, and improve the cycle stability of the lithium-sulfur battery by adding MXene, a material with excellent conductive properties, into the conductive agent.
[0043] (5) The raw materials of the present invention are cheap and easily available, and the synthesis method is simple. The product can be synthesized by simple heating and stirring, without the need for complicated reaction steps and separation and purification steps. The reaction time is short, energy and cost are saved, and the method is easy to implement and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The cycle performance and coulombic efficiency of the lithium-sulfur batteries of Examples 1-5 of the present invention at a current density of 0.2C. DETAILED DESCRIPTION
[0045] The present invention is further described in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto. The raw materials and reagents involved in the following examples can be obtained from commercial channels. It should be noted that the "first mixed solution" and "second mixed solution" referred to in the examples are only for distinguishing different solutions and do not constitute a limitation of the present invention.
[0046] In the following examples, the stirring speed is 350 rpm. The electrolyte used is composed of 1 mol / L lithium bis(trifluoromethylsulfonyl)imide in 1,3-dioxolane / ethylene glycol dimethyl ether, wherein the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:1.
[0047] Example 1
[0048] The preparation method of the lithium-sulfur battery of this embodiment comprises the following steps:
[0049] (1) Weigh 1 g of sodium dodecyl sulfate and add it to 100 mL of water. Then transfer the mixture into a three-necked flask and stir it magnetically to obtain a first mixed solution.
[0050] (2) Weigh 0.1 g of potassium persulfate initiator and add it to the first mixed solution, and continue magnetic stirring to obtain a second mixed solution.
[0051] (3) The second mixed solution was heated until the solution temperature reached 70°C, 5 g of acrylonitrile was measured and transferred to a dropping funnel, and then uniformly dripped into the above three-necked flask. The dripping was completed within 5 min. The three-necked flask was heated to 70°C in an oil bath and maintained for 1 h to allow the units in the three-necked flask to polymerize. After the reaction was completed, a polyacrylonitrile solution was obtained.
[0052] (4) The polyacrylonitrile solution is centrifuged, and then the solid product obtained by centrifugation is freeze-dried to obtain a white powder, which is polyacrylonitrile.
[0053] (5) After ball milling 4 g of polyacrylonitrile and 16 g of sublimed sulfur (mass ratio of 1:4), the mixture was dried in a vacuum drying oven at 60°C for 24 h, and then the gas was replaced in a glove box filled with argon. The mixture was immediately subjected to high-temperature heat treatment in a tubular furnace for 6 h at a temperature of 300°C. Argon was used as a protective gas throughout the process. After the reaction was completed, the reaction product was cooled to room temperature. The collected black powder was the sulfide polyacrylonitrile material.
[0054] (6) 0.14 g of sulfided polyacrylonitrile, 0.04 g of conductive agent Super P, and 0.02 g of commercial binder PVDF were mixed (active material, conductive agent, and binder were configured in a mass ratio of 7:2:1), and the electrode slurry was uniformly obtained by ball milling. The electrode slurry was coated on the current collector aluminum foil with a coating thickness of 500 μm to obtain a lithium-sulfur battery positive electrode sheet.
[0055] (7) Assemble a 2016 model battery by placing a lithium metal negative electrode sheet of a lithium-sulfur battery, a positive electrode sheet of a lithium-sulfur battery, a polypropylene separator and an electrolyte in an argon glove box with a water content of less than 10 ppm.
[0056] Example 2
[0057] The preparation method of the lithium-sulfur battery of this embodiment comprises the following steps:
[0058] (1) Weigh 0.5 g of sodium dodecyl sulfate, add it to 100 mL of water, and then transfer it to a three-necked flask and stir it magnetically to obtain a first mixed solution.
[0059] (2) Weigh 0.1 g of potassium persulfate initiator and add it to the first mixed solution, and continue magnetic stirring to obtain a second mixed solution.
[0060] (3) The second mixed solution was heated until the solution temperature reached 70°C, 5 g of acrylonitrile was measured and transferred to a dropping funnel, and then uniformly dripped into the above three-necked flask. The dripping was completed within 5 min. The three-necked flask was heated to 70°C in an oil bath and maintained for 1 h to allow the units in the three-necked flask to polymerize. After the reaction was completed, a polyacrylonitrile solution was obtained.
[0061] (4) The polyacrylonitrile solution is centrifuged, and then the solid product obtained by centrifugation is freeze-dried to obtain a white powder, which is polyacrylonitrile.
[0062] (5) After ball milling 4 g of polyacrylonitrile and 16 g of sublimed sulfur (mass ratio of 1:4), the mixture was dried in a vacuum drying oven at 60°C for 24 h, and then the gas was replaced in a glove box filled with argon. The mixture was immediately subjected to high-temperature heat treatment in a tubular furnace for 6 h at a temperature of 300°C. Argon was used as a protective gas throughout the process. After the reaction was completed, the reaction product was cooled to room temperature. The collected black powder was the sulfide polyacrylonitrile material.
[0063] (6) 0.14 g of sulfided polyacrylonitrile, 0.04 g of conductive agent Super P, and 0.02 g of commercial binder PVDF were mixed (active material, conductive agent, and binder were configured in a mass ratio of 7:2:1), and the electrode slurry was uniformly obtained by ball milling. The electrode slurry was coated on the current collector aluminum foil with a coating thickness of 500 μm to obtain a lithium-sulfur battery positive electrode sheet.
[0064] (7) Assemble a 2016 model battery by placing a lithium metal negative electrode sheet of a lithium-sulfur battery, a positive electrode sheet of a lithium-sulfur battery, a polypropylene separator and an electrolyte in an argon glove box with a water content of less than 10 ppm.
[0065] Example 3
[0066] The preparation method of the lithium-sulfur battery of this embodiment comprises the following steps:
[0067] (1) Weigh 2 g of sodium dodecyl sulfate and add it to 100 mL of water. Then transfer the mixture into a three-necked flask and stir it magnetically to obtain a first mixed solution.
[0068] (2) Weigh 0.1 g of potassium persulfate initiator and add it to the first mixed solution, and continue magnetic stirring to obtain a second mixed solution.
[0069] (3) The second mixed solution was heated until the solution temperature reached 70°C, 5 g of acrylonitrile was measured and transferred to a dropping funnel, and then uniformly dripped into the above three-necked flask. The dripping was completed within 5 min. The three-necked flask was heated to 70°C in an oil bath and maintained for 1 h to allow the units in the three-necked flask to polymerize. After the reaction was completed, a polyacrylonitrile solution was obtained.
[0070] (4) The polyacrylonitrile solution is centrifuged, and then the solid product obtained by centrifugation is freeze-dried to obtain a white powder, which is polyacrylonitrile.
[0071] (5) After ball milling 4 g of polyacrylonitrile and 16 g of sublimed sulfur (mass ratio of 1:4), the mixture was dried in a vacuum drying oven at 60°C for 24 h, and then the gas was replaced in a glove box filled with argon. The mixture was immediately subjected to high-temperature heat treatment in a tubular furnace for 6 h at a temperature of 300°C. Argon was used as a protective gas throughout the process. After the reaction was completed, the reactants were cooled to room temperature. The collected black powder was the sulfide polyacrylonitrile material.
[0072] (6) 0.14 g of sulfided polyacrylonitrile, 0.04 g of conductive agent Super P, and 0.02 g of commercial binder PVDF were mixed (active material, conductive agent, and binder were configured in a mass ratio of 7:2:1), and the electrode slurry was uniformly obtained by ball milling. The electrode slurry was coated on the current collector aluminum foil with a coating thickness of 500 μm to obtain a lithium-sulfur battery positive electrode sheet.
[0073] (7) Assemble a 2016 model battery by placing a lithium metal negative electrode sheet of a lithium-sulfur battery, a positive electrode sheet of a lithium-sulfur battery, a polypropylene separator and an electrolyte in an argon glove box with a water content of less than 10 ppm.
[0074] Example 4
[0075] The preparation method of the lithium-sulfur battery of this embodiment comprises the following steps:
[0076] (1) Weigh 4 g of sodium dodecyl sulfate, add it to 100 mL of water, then transfer it to a three-necked flask and stir it magnetically to obtain a first mixed solution.
[0077] (2) Weigh 0.1 g of potassium persulfate initiator and add it to the first mixed solution, and continue magnetic stirring to obtain a second mixed solution.
[0078] (3) The second mixed solution was heated until the solution temperature reached 70°C, 5 g of acrylonitrile was measured and transferred to a dropping funnel, and then uniformly dripped into the above three-necked flask. The dripping was completed within 5 min. The three-necked flask was heated to 70°C in an oil bath and maintained for 1 h to allow the units in the three-necked flask to polymerize. After the reaction was completed, a polyacrylonitrile solution was obtained.
[0079] (4) The polyacrylonitrile solution is centrifuged, and then the solid product obtained by centrifugation is freeze-dried to obtain a white powder, which is polyacrylonitrile.
[0080] (5) After ball milling 4 g of polyacrylonitrile and 16 g of sublimed sulfur (mass ratio of 1:4), the mixture was dried in a vacuum drying oven at 60°C for 24 h, and then the gas was replaced in a glove box filled with argon. The mixture was immediately subjected to high-temperature heat treatment in a tubular furnace for 6 h at a temperature of 300°C. Argon was used as a protective gas throughout the process. After the reaction was completed, the reaction product was cooled to room temperature. The collected black powder was the sulfide polyacrylonitrile material.
[0081] (6) 0.14 g of sulfided polyacrylonitrile, 0.04 g of conductive agent Super P, and 0.02 g of commercial binder PVDF were mixed (active material, conductive agent, and binder were configured in a mass ratio of 7:2:1), and the electrode slurry was uniformly obtained by ball milling. The electrode slurry was coated on the current collector aluminum foil with a coating thickness of 500 μm to obtain a lithium-sulfur battery positive electrode sheet.
[0082] (7) Assemble a 2016 model battery by placing a lithium metal negative electrode sheet of a lithium-sulfur battery, a positive electrode sheet of a lithium-sulfur battery, a polypropylene separator and an electrolyte in an argon glove box with a water content of less than 10 ppm.
[0083] Example 5
[0084] The preparation method of the lithium-sulfur battery of this embodiment comprises the following steps:
[0085] (1) Weigh 1 g of sodium dodecyl sulfate and add it to 100 mL of water. Then transfer the mixture into a three-necked flask and stir it magnetically to obtain a first mixed solution.
[0086] (2) Weigh 0.1 g of potassium persulfate initiator and add it to the first mixed solution, and continue magnetic stirring to obtain a second mixed solution.
[0087] (3) The second mixed solution was heated until the solution temperature reached 70°C, 5 g of acrylonitrile solution was measured and transferred to a dropping funnel, and then uniformly dripped into the above three-necked flask. The dripping was completed within 5 min. The three-necked flask was heated to 70°C in an oil bath and maintained for 1 h to allow the units in the three-necked flask to polymerize. After the reaction was completed, a polyacrylonitrile solution was obtained.
[0088] (4) The polyacrylonitrile solution is centrifuged, and then the solid product obtained by centrifugation is freeze-dried to obtain a white powder, which is polyacrylonitrile.
[0089] (5) After ball milling 4 g of polyacrylonitrile and 16 g of sublimed sulfur (mass ratio of 1:4), the mixture was dried in a vacuum drying oven at 60°C for 24 h, and then the gas was replaced in a glove box filled with argon. The mixture was immediately subjected to high-temperature heat treatment in a tubular furnace for 6 h at a temperature of 300°C. Argon was used as a protective gas throughout the process. After the reaction was completed, the reaction product was cooled to room temperature. The collected black powder was the sulfide polyacrylonitrile material.
[0090] (6) 0.16 g of sulfide polyacrylonitrile, 0.01 g of conductive agent Super P, 0.01 g of MXene material (concentration of 5 mg / mL) and 0.02 g of aqueous binder polyacrylate were mixed (active material, conductive agent, MXene material, binder were configured in a mass ratio of 16:1:1:2), and the electrode slurry was evenly obtained by ball milling. The electrode slurry was coated on the current collector aluminum foil with a coating thickness of 750 μm to obtain a lithium-sulfur battery positive electrode sheet.
[0091] (7) Assemble a 2016 model battery by placing a lithium metal negative electrode sheet of a lithium-sulfur battery, a positive electrode sheet of a lithium-sulfur battery, a polypropylene separator and an electrolyte in an argon glove box with a water content of less than 10 ppm.
[0092] In the above Examples 1-5, the difference between Examples 1-4 is only the different amounts of sodium dodecyl sulfate, and the difference between Example 1 and Example 5 is only the different conductive agents added.
[0093] Next, in order to explore the cycle stability of the battery prepared using the sulfide polyacrylonitrile of the present invention as the positive electrode material of the lithium-sulfur battery, and the factors affecting the cycle stability of the battery prepared using the sulfide polyacrylonitrile of the present invention as the positive electrode material of the lithium-sulfur battery, the lithium-sulfur batteries prepared in Examples 1-5 were subjected to cycle tests.
[0094] Test method: Use Shenzhen Xinwei Company's CT2001A battery tester to perform constant current charge and discharge tests on the battery.
[0095] Test conditions: The voltage range of the constant current charge and discharge test is 1-3V and the current rate is 0.2C.
[0096] Test results: The cycle performance and coulombic efficiency of the batteries of Examples 1-5 are as follows: Figure 1 As shown. Figure 1 It can be seen that:
[0097] (1) For the lithium-sulfur battery assembled with the polyacrylonitrile sulfide material prepared with 1 g of sodium dodecyl sulfate in Example 1, the capacity can still be maintained at 1360 mAh g after 200 cycles at a current rate of 0.2 C. -1 , the coulombic efficiency is 99.8%; the capacity of the battery in Example 2 drops to 706 mAh g after 200 cycles at a current rate of 0.2 C. -1 , but the coulombic efficiency is still close to 100%; the battery of Example 3 has a capacity of 664 mAhg after 200 cycles at a current rate of 0.2C. -1 , the coulombic efficiency is 99.7%; the capacity of the battery in Example 4 dropped to 554 mAh g after 200 cycles at a current rate of 0.2 C. -1, the coulombic efficiency is 99.7%; the battery of Example 5 can still maintain a capacity of 1036 mAh g after 200 cycles at a current rate of 0.2C. -1 , and the coulombic efficiency is 99.9%. This shows that the use of polyacrylonitrile material generated by free radical polymerization of 1g of sodium dodecyl sulfate and acrylonitrile monomer and the sulfurized polyacrylonitrile material sintered by sublimated sulfur at high temperature in lithium-sulfur batteries can more effectively alleviate the volume effect during the charging and discharging process of lithium-sulfur batteries, thereby maintaining the battery's cycle stability and excellent capacity retention rate.
[0098] In Examples 1-4, the feed amount of sodium dodecyl sulfate is 0.01, 0.005, 0.02, and 0.04 g / mL, respectively, and the particle sizes of the prepared polyacrylonitrile materials are 90, 45, 180, and 260 nm, respectively. These polyacrylonitrile materials of different particle sizes are mixed with sublimated sulfur and loaded into lithium batteries. According to the battery performance, it can be seen that when Example 1 is selected, that is, the feed amount of the emulsifier sodium dodecyl sulfate is 0.01 g / mL, the particle size of the prepared polyacrylonitrile is 90 nm, and the lithium battery loaded with the battery can still maintain a discharge capacity of 1360 mAh g after 200 cycles at a high rate of 0.2C. -1 , the capacity retention rate is 99.8%.
[0099] (2) By comparing the electrochemical performance of the battery of Example 5 with that of Examples 2, 3, and 4, it can be found that after adding MXene material, the coulombic efficiency of the prepared lithium-sulfur battery is high, and the capacity can still be maintained at 1036 mAh g after 200 cycles. -1 , its capacity retention rate is significantly higher than that of Examples 2, 3, and 4, the capacity is more stable, and the cycle stability is better. This is because the degree of cyclization of the sulfided polyacrylonitrile obtained by directly heat-treating polyacrylonitrile and sulfur is not high, that is, fewer conjugated bonds are formed, so that the conductivity of the sulfided polyacrylonitrile is low. Adding MXene materials to the conductive agent can enhance the conductivity of the lithium-sulfur battery and alleviate the volume expansion during the charge and discharge process, thereby maintaining the cycle stability of the battery and the optimal capacity retention rate.
[0100] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the present application.
Claims
1. A method for preparing a vulcanized polyacrylonitrile material, characterized in that: The following steps are involved: (1) adding sodium dodecyl sulfate into water and stirring to obtain a first mixed solution; (2) adding potassium persulfate to the first mixed solution and continuing stirring to obtain a second mixed solution; (3) The second mixed solution is heated until the solution temperature reaches 70°C, acrylonitrile is added, and the mixture is stirred and nitrogen is passed through the mixture. The mixture is kept at 70°C for 1 hour. After the reaction is completed, a polyacrylonitrile solution is obtained. (4) centrifuging the polyacrylonitrile solution and freeze-drying the solid product obtained by centrifugation to obtain polyacrylonitrile; (5) mixing polyacrylonitrile and sulfur powder and subjecting them to high-temperature heat treatment to obtain a sulfurized polyacrylonitrile material; The mass ratio of the sodium dodecyl sulfate, water, potassium persulfate and acrylonitrile is 1:100:0.1:
5.
2. The method for preparing the vulcanized polyacrylonitrile material according to claim 1, characterized in that: The mass ratio of the polyacrylonitrile to the sulfur powder is 1:
4.
3. The method for preparing the vulcanized polyacrylonitrile material according to claim 1 or 2, characterized in that: The temperature of the high temperature heat treatment is 300-600° C. and the time is 6-8 hours.
4. A method for preparing a positive electrode of a lithium-sulfur battery, characterized in that: The following steps are involved: A sulfurized polyacrylonitrile material is prepared according to the preparation method according to any one of claims 1 to 3, and then the prepared sulfurized polyacrylonitrile material is mixed with a conductive agent, an oily binder, or a conductive agent, a MXene material and an aqueous binder and ball-milled to prepare an electrode slurry, and then the slurry is uniformly coated on a current collector and dried to obtain a lithium-sulfur battery positive electrode.
5. The method for preparing a positive electrode of a lithium-sulfur battery according to claim 4, characterized in that: The mass ratio of the vulcanized polyacrylonitrile material to the conductive agent and the oily binder is 7:2:1, and the mass ratio of the vulcanized polyacrylonitrile material to the conductive agent, the MXene material and the aqueous binder is 16:1:1:2.
Citation Information
Patent Citations
Modifying method for improving electrochemical performance of lithium iron phosphate anode material
CN108899479A